Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Sure, let's solve the equation [tex]\(\log_2 x - \log_2(x + 3) = -21\)[/tex] step-by-step.
1. Recall the properties of logarithms:
Using the property of logarithms that states [tex]\(\log_a b - \log_a c = \log_a \left(\frac{b}{c}\right)\)[/tex], we can rewrite the left-hand side of the equation.
[tex]\[ \log_2 x - \log_2 (x + 3) = \log_2 \left(\frac{x}{x + 3}\right) \][/tex]
Thus, the equation becomes:
[tex]\[ \log_2 \left(\frac{x}{x + 3}\right) = -21 \][/tex]
2. Exponentiate both sides to remove the logarithm:
To eliminate the logarithm, we raise 2 to the power of both sides of the equation, using the fact [tex]\(a^{\log_a b} = b\)[/tex]. Hence:
[tex]\[ 2^{\log_2 \left(\frac{x}{x + 3}\right)} = 2^{-21} \][/tex]
This simplifies to:
[tex]\[ \frac{x}{x + 3} = 2^{-21} \][/tex]
3. Solve the resulting equation:
To solve for [tex]\(x\)[/tex], multiply both sides by [tex]\(x + 3\)[/tex] to clear the fraction:
[tex]\[ x = 2^{-21} (x + 3) \][/tex]
Distribute [tex]\(2^{-21}\)[/tex] on the right-hand side:
[tex]\[ x = \frac{1}{2^{21}} x + \frac{3}{2^{21}} \][/tex]
4. Isolate [tex]\(x\)[/tex]:
To isolate [tex]\(x\)[/tex], first move the [tex]\(\frac{1}{2^{21}} x\)[/tex] term to the left-hand side:
[tex]\[ x - \frac{1}{2^{21}} x = \frac{3}{2^{21}} \][/tex]
Factor [tex]\(x\)[/tex] out of the left-hand side:
[tex]\[ x \left(1 - \frac{1}{2^{21}}\right) = \frac{3}{2^{21}} \][/tex]
5. Simplify the expression:
Recognize that [tex]\(1 - \frac{1}{2^{21}} = \frac{2^{21} - 1}{2^{21}}\)[/tex], so the equation becomes:
[tex]\[ x \cdot \frac{2^{21} - 1}{2^{21}} = \frac{3}{2^{21}} \][/tex]
6. Solve for [tex]\(x\)[/tex]:
To isolate [tex]\(x\)[/tex], multiply both sides by [tex]\(\frac{2^{21}}{2^{21} - 1}\)[/tex]:
[tex]\[ x = \frac{3}{2^{21} - 1} \][/tex]
Simplify to get:
[tex]\[ x = \frac{3}{2^{21} - 1} = \frac{3}{2097151} \][/tex]
So, the solution to the equation [tex]\(\log_2 x - \log_2(x + 3) = -21\)[/tex] is:
[tex]\[ x = \frac{3}{2097151} \][/tex]
1. Recall the properties of logarithms:
Using the property of logarithms that states [tex]\(\log_a b - \log_a c = \log_a \left(\frac{b}{c}\right)\)[/tex], we can rewrite the left-hand side of the equation.
[tex]\[ \log_2 x - \log_2 (x + 3) = \log_2 \left(\frac{x}{x + 3}\right) \][/tex]
Thus, the equation becomes:
[tex]\[ \log_2 \left(\frac{x}{x + 3}\right) = -21 \][/tex]
2. Exponentiate both sides to remove the logarithm:
To eliminate the logarithm, we raise 2 to the power of both sides of the equation, using the fact [tex]\(a^{\log_a b} = b\)[/tex]. Hence:
[tex]\[ 2^{\log_2 \left(\frac{x}{x + 3}\right)} = 2^{-21} \][/tex]
This simplifies to:
[tex]\[ \frac{x}{x + 3} = 2^{-21} \][/tex]
3. Solve the resulting equation:
To solve for [tex]\(x\)[/tex], multiply both sides by [tex]\(x + 3\)[/tex] to clear the fraction:
[tex]\[ x = 2^{-21} (x + 3) \][/tex]
Distribute [tex]\(2^{-21}\)[/tex] on the right-hand side:
[tex]\[ x = \frac{1}{2^{21}} x + \frac{3}{2^{21}} \][/tex]
4. Isolate [tex]\(x\)[/tex]:
To isolate [tex]\(x\)[/tex], first move the [tex]\(\frac{1}{2^{21}} x\)[/tex] term to the left-hand side:
[tex]\[ x - \frac{1}{2^{21}} x = \frac{3}{2^{21}} \][/tex]
Factor [tex]\(x\)[/tex] out of the left-hand side:
[tex]\[ x \left(1 - \frac{1}{2^{21}}\right) = \frac{3}{2^{21}} \][/tex]
5. Simplify the expression:
Recognize that [tex]\(1 - \frac{1}{2^{21}} = \frac{2^{21} - 1}{2^{21}}\)[/tex], so the equation becomes:
[tex]\[ x \cdot \frac{2^{21} - 1}{2^{21}} = \frac{3}{2^{21}} \][/tex]
6. Solve for [tex]\(x\)[/tex]:
To isolate [tex]\(x\)[/tex], multiply both sides by [tex]\(\frac{2^{21}}{2^{21} - 1}\)[/tex]:
[tex]\[ x = \frac{3}{2^{21} - 1} \][/tex]
Simplify to get:
[tex]\[ x = \frac{3}{2^{21} - 1} = \frac{3}{2097151} \][/tex]
So, the solution to the equation [tex]\(\log_2 x - \log_2(x + 3) = -21\)[/tex] is:
[tex]\[ x = \frac{3}{2097151} \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.